Construction of AFLP-based cosegregation groups of tetraploid Plicatula species and identification of markers linked to apomixis - Aguilera, Patricia Mabel (2022)
Most species of Plicatula are important native forages. This work aimed to build framework cosegregation groups of the apomictic tetraploid race of Paspalum guenoarum cv. Rojas and localize the locus controlling apomixis in the species. An interspecific population derived from crossing a completely sexual tetraploid plant of P. plicatulum and an apomictic tetraploid individual of P. guenoarum cv. Rojas was used. Both, disomic and tetrasomic inheritance were detected in both parental genotypes. In P. guenoarum, ten cosegregation groups were built, including 50 markers expanding for 583 cM. The estimated genome coverage was 63.95%. The apomixis locus was located in the linkage group M8, together with seven other loci (four paternal and three biparental markers). The group extended for 59 cM. The four paternal markers showed strong linkage to apomixis, and two of them mapped at 4 and 7 cM at both sides of the locus. Five female linkage groups were constructed with markers segregating from P. plicatulum. One of them (F3) being homologous to the male group carrying apomixis. The linkage groups presented here constitute the first genetic frame for species of Plicatula group. Moreover, molecular markers linked to apomixis in P. guenoarum can assist fundamental research and breeding programs.